Non-equiatomic W10Mo27Cr21Ti22Al20 high-entropy alloy produced by mechanical alloying and spark plasma sintering: Phase evolution and mechanical properties. (April 2022) - Naser-Zoshki, Hamed; Kiani-Rashid, Ali-Reza; Vahdati-Khaki, Jalil
In this work, non-equiatomic W10 Mo27 Cr21 Ti22 Al20 refractory high-entropy alloy (RHEA) was produced using mechanical alloying followed by spark plasma sintering. The phase formation, microstructure, and compressive mechanical properties of the alloy were studied. During mechanical alloying, a Body-centered cubic (BCC) solid solution phase with a particle size of less than 1 µm was obtained after 18 h ball milling. The microstructure of the sintered sample exhibits three distinct phases consisting of two solid solution phases BCC1 and BCC2 as well as fine TiCx Oy precipitates distributed in them. The volume fractions of each phase were about 79%, 8%, and 13%, respectively. The sintered W10 Mo27 Cr21 Ti22 Al20 showed yield strengths of 2465, 1506, 405, and 290 MPa at room temperature 600, 1000, and 1200°C, respectively, which are about twice that of the same refractory high-entropy alloy produced by vacuum arc melting. At 1000 and 1200°C, the strength after yielding gradually increased to 970 and 718 MPa at a compressive strain of 60%. The studied refractory high-entropy alloy can have good potential in high-temperature applications due to its high specific strength at elevated temperatures compared to conventional Ni-based superalloys and most as-reported refractory high-entropy alloys.